2003
DOI: 10.1002/chem.200204167
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Coordination of the Azido Bridge in the Magnetic Coupling of Copper(II) Binuclear Complexes

Abstract: It is well-known that the azido bridge gives rise antiferromagnetic (AF) or ferromagnetic (F) coupling depending on its coordination mode, namely end-to-end or end-on, respectively. The aim of the present work is to analyse the factors contributing to this different magnetic behaviour. The difference dedicated configuration interaction (DDCI) method is applied to several binuclear Cu(II) azido-bridged models with both types of coordination. In end-on complexes, the direct exchange and the spin polarisation con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 66 publications
1
52
0
Order By: Relevance
“…Many calculations have shown the performance of DDCI estimates of the magnetic coupling. [20][21][22][23][24][25][26][27][28][29][30][31][32] The results reported in Table I show that the J values obtained at CAS+ S and DDCI2 levels are far from experimental ones, which suggest that an important part of the effects is missed. It is therefore concluded that 2h-1p and 1h-2p configurations bring from 30% to 50% of magnetic coupling.…”
Section: ͑8͒mentioning
confidence: 90%
See 1 more Smart Citation
“…Many calculations have shown the performance of DDCI estimates of the magnetic coupling. [20][21][22][23][24][25][26][27][28][29][30][31][32] The results reported in Table I show that the J values obtained at CAS+ S and DDCI2 levels are far from experimental ones, which suggest that an important part of the effects is missed. It is therefore concluded that 2h-1p and 1h-2p configurations bring from 30% to 50% of magnetic coupling.…”
Section: ͑8͒mentioning
confidence: 90%
“…So far, the DDCI approach has been extensively employed in the evaluation of J in molecular and solid state magnetic materials with a remarkable good agreement with experiment. [20][21][22][23][24][25][26][27][28][29][30][31][32] Some years ago we took benefit of this methodology to analyze in depth the physical contributions to the magnetic coupling on a series of binuclear Cu ͑II͒ complexes. 33 The use of the DDCI strategy allows not only to obtain quite accurate J values but also to analyze the various physical effects by generating CI spaces of increasing lengths that include different types of determinants.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some purely ab initio approaches have already tackled that problem. [100][101][102][103][104][105][106] In this section, we will illustrate how SF-DFT computations can help in designing such a space. The starting idea is very simple: as SF-DFT computations are not the limiting CPU-time step if aiming at performing a pure high-level ab initio multireference correlated computation, then, let us first perform a SF-DFT computation and retain in the zeroth-order space to be built only those electrons and orbitals involved in the final SF-DFT wave functions.…”
Section: Application: Designing Zeroth-order Variational Spaces Fomentioning
confidence: 99%
“…As evidenced from Table 1, several structural parameters have to be considered: not only the coordination geometry, [34] but also the CuÀN bond lengths or the Cu-N-N-Cu torsion angle, as recently pointed out. [11,23] Obviously, the azido bridge is non-innocent in the exchange process [29] Therefore, even weak ferromagnetic coupling in EE systems still deserves attention.…”
mentioning
confidence: 99%